PENGELOLAAN SUMBER DAYA SEKOLAH SECARA EFEKTIF DAN EFISIEN SELAMA MASA PANDEMI COVID 19 PADA SEKOLAH DASAR NEGERI No. 14 ROMO DUGINANG - Samuddin Samuddin (STKIP NU Kabupaten Tegal, 2022)
The COVID-19 pandemic has had a huge impact on the implementation of education in Indonesia, from big cities to small cities. This situation has drastically changed the face-to-face learning system into online learning which in the end forced educators to adapt in utilizing technology in delivering learning materials to students. This situation is also a challenge for the principal as a manager in a school who plays an important role in the success of education. The purpose of this paper is to find out, explain and analyze the management of school resources at SDN No. 14 Romo Duginang during the covid-19 pandemic. The method used in writing scientific articles uses interviews with educators, students and parents of students as well as literature review related to conditions in the field and then the data will be analyzed descriptively.